2014
DOI: 10.1080/10454438.2014.901077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Protein Level on Growth Performance and Blood Parameters of Marbled SpinefootSiganus rivulatus

Abstract: The present study evaluated the effect of dietary protein levels on growth performance and blood parameters of juvenile marbled spinefoot ( Siganus rivulatus). Five semipurified, isoenergetic (14.2 MJ digestible energy/kg; 84 g lipids/kg) diets were formulated to contain 30, 35, 40, 45, and 50 g crude protein (CP)/100 g diet. Groups of 15 juvenile fish (7.4 g individual weight) were randomly assigned in triplicate to each of the five treatments and offered the test diets three times daily ad libitum for 9 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…A total of four experimental diets were formulated to be isonitrogenous (crude protein: 34.39%), isolipidic (crude lipid: 9.81%) and isocaloric (gross energy: 20.57 kJ g −1 ) as pre-determined requirements of S. rivulatus according to Ghanawi, et al [44]; El-Dakar, et al [45] and Abou-Daoud, et al [46], and shown in Table 1. The control diet was prepared without LTN or BS supplementation (Control), and the other three diets were control diet supplemented with BS (0.15 g kg −1 ; Handan Qinyueming Metal Products Co. Ltd., Hebei, China), LTN (0.1 g kg −1 ; Jeevan Chemicals and Pharmaceuticals Co., Maharashtra, India) and combination of BS+LTN (0.15 and 0.1 g kg −1 , respectively).…”
Section: Experimental Diets Formulationmentioning
confidence: 99%
“…A total of four experimental diets were formulated to be isonitrogenous (crude protein: 34.39%), isolipidic (crude lipid: 9.81%) and isocaloric (gross energy: 20.57 kJ g −1 ) as pre-determined requirements of S. rivulatus according to Ghanawi, et al [44]; El-Dakar, et al [45] and Abou-Daoud, et al [46], and shown in Table 1. The control diet was prepared without LTN or BS supplementation (Control), and the other three diets were control diet supplemented with BS (0.15 g kg −1 ; Handan Qinyueming Metal Products Co. Ltd., Hebei, China), LTN (0.1 g kg −1 ; Jeevan Chemicals and Pharmaceuticals Co., Maharashtra, India) and combination of BS+LTN (0.15 and 0.1 g kg −1 , respectively).…”
Section: Experimental Diets Formulationmentioning
confidence: 99%
“…Wild S. rivulatus is a coastal dweller feeding on various macrophytes (Anastasiades, 2011). Rabbitfish has been found as a potential warm water candidate for marine aquaculture production due to its good taste and being omnivore feeding on artificial diets (Lam, 1974;Abou-Daoud et al, 2014). Thus, it can provide a cheap protein source on a large production scale.…”
Section: Introductionmentioning
confidence: 99%